Factors Influencing Organization Success: A Case Study of Walmart - Pandey, Rudresh; D, Dillip; Jayant, Jigyasa; Vashishth, Kajal; Nikhil, Nikhil; Qi, Tin Jin; Kee, Daisy Mui Hung; Mei, Tan Cai; Xin, Roselin Yong Kai; Qhi, Looi Yong (AIBPM Publisher, 2021)
Walmart was established by Sam Walton and beginning as a small discount retailer in Rogers, Arkansas in 1962. This paper investigates how Walmart become popular and successful in retail business around the world and how they perform well in sales. This study found that some factors were leading to the success of Walmart. Since then, Walmart has become the most trusted retailer that creates value for business and society.